Tratamiento de la NICSP 33 en los estados financieros de los gobiernos descentralizados municipales - Yagual Aguirre, Luis Andre (2022)
The following work whose main topic is Treatment of NICSP 33 in the financial statements of the Autonomous Decentralized Municipal Governments, where a very common problem in Ecuador has been investigated, such as the misuse of public resources, aims to investigate the Effect of Treatment in this NICSP In the first chapter the situation of the problem is put into context in order to proceed to the investigation, in the second chapter, the theoretical framework where contextualization is also presented; The third chapter of the methodology will present the methods and approaches to be treated; In chapter four, the research proposal will be presented, where a technical report on the effect of the NICSP 33 treatment on the financial statements of the municipal GADs will be presented. Finally, the conclusions and recommendations will be presented......